Characterisation of nematode symbiotic bacteria and the in vitro liquid culture of Heterorhabditis zealandica and Steinernema yirgalemense - Ferreira, Tiarin (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.